2008
DOI: 10.33585/cmy.60106
|View full text |Cite
|
Sign up to set email alerts
|

Mycobiota associated with baby food products imported into Uganda with special reference to aflatoxigenic aspergilli and aflatoxins.

Abstract: Five baby food products imported into Uganda were collected from different shops and investigated for contamination by fungi and aflatoxins. Forty-two species belonging to 21 genera in addition to some unidentified fungi were recovered on dichloran rose bengal chloramphenicol agar. Cornflakes followed by Cerelac were the most heavily contaminated products while Heinz mixed cereal was the least. Cladosporium sphaerospermum, Fusarium tricinctum and Penicillium oxalicum were the most predominant fungi. On the oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 37 publications
4
9
0
Order By: Relevance
“…The tested cerelac sample was aflatoxin‐free, although this sample had aflatoxigenic aspergilli isolate. The same result was recorded by Ismail et al who showed that the absence of aflatoxins in cerelac may be due to its low moisture content. Abdalla et al reported that inhibition and reduction in fungal activity depended on sample's moisture content.…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…The tested cerelac sample was aflatoxin‐free, although this sample had aflatoxigenic aspergilli isolate. The same result was recorded by Ismail et al who showed that the absence of aflatoxins in cerelac may be due to its low moisture content. Abdalla et al reported that inhibition and reduction in fungal activity depended on sample's moisture content.…”
Section: Resultssupporting
confidence: 84%
“…Thirty‐two species comprising twelve genera were isolated from the tested samples on GPY medium; cornflakes were heavily contaminated with fungi (24 species including 9 genera), cerelac came in the second position where it contaminated with 18 species and 10 genera, and milk powder was the latest with 11 species and 7 genera as shown in Table . This finding was previously proved by Ismail et al who reported that cornflakes and cerelac were the highest contaminated baby food products.…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations